Modulus estimation of polymers via nanoindentation – impact of surface roughness, peak force and testing speed - Michael Huszar; Gernot Oreski; Florian Arbeiter (Acta Polytechnica CTU Proceedings)
Nanoindentation is widely used to study small-scale structures in materials. The impact of varying testing conditions on the measurement’s accuracy is of high interest, and their influence on the characterization of polymeric materials is still quite scarce. Therefore, this study investigates varying loading and unloading rates paired with maximum loads ranging from 0.5 to 20 mN on Polyethylene samples with varying surface finishes after wet grinding. The indentation Data was analyzed using the Oliver & Pharr Method, and the resulting Modulus was compared with those obtained from macroscopical tensile tests. The hardness was compared to Shore hardness measurements. A correlation between the measured modulus values and the surface Quality was explored. The results prove the already established rule that the best surface finish (Sa = 0.07 μm) leads to the smallest standard deviation. However, they show that the modulus characterization is less influenced by surface roughness than hardness evaluations.